THE IMPACTS OF OIL PRICE AND GOLD PRICE ON VIETNAM’S STOCK MARKET BEFORE AND DURING COVID-19 PANDEMIC - Ho Hoang Gia Bao; Hoang Phong Le; Thanh Huu Phu Nguyen (Scientific Results, 2024)
This paper evaluates the impacts of oil and gold prices on the two major indices of Vietnam (VN-Index and HNX-Index) using the daily data from January 2010 to November 2020 and the GARCH(1,1) model. We find that oil price positively affects VN-Index and HNX-Index before and during the COVID-19 pandemic. However, there is no significant effect of gold price, which implies its role as a weak safe haven asset and a weak hedge asset. While the COVID-19 pandemic does not influence on VN-Index, it has a small positive impact on HNX-Index. In addition, the COVID-19 pandemic raises the impact of oil price on the two indices.